2011
DOI: 10.1111/j.1574-695x.2011.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis polysaccharide intercellular adhesin activates complement

Abstract: Staphylococcus epidermidis is a frequent cause of nosocomial infections. The central virulence factor of S. epidermidis is biofilm formation. Polysaccharide intercellular adhesin (PIA) constitutes the major biofilm matrix-component. PIA and biofilm have been implicated in S. epidermidis evasion of host immune defence. We examined the effects of S. epidermidis PIA on the inflammatory response with focus on complement activation. We used a human whole-blood ex vivo model of infection and compared the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
35
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 46 publications
7
35
0
4
Order By: Relevance
“…A lower activity of the alternative amplification loop may also explain why we observed lower levels of activation products of the final common pathway in cord blood. We have previously shown that PIA biofilm and purified PIA induced a strong complement activation (23). Similar findings were observed in the current study.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…A lower activity of the alternative amplification loop may also explain why we observed lower levels of activation products of the final common pathway in cord blood. We have previously shown that PIA biofilm and purified PIA induced a strong complement activation (23). Similar findings were observed in the current study.…”
Section: Discussionsupporting
confidence: 82%
“…The PIA biofilm induced markedly stronger complement activation than the non-PIA biofilm, both in adult and cord blood. Collectively, these data support our hypothesis that PIA is a complement activator (10,23) in neonates as well.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations